Consumer Perceived Value Analysis of New & Incumbent Brands of Gudang Garam & Sampoerna - Nasution, Reza Ashari; Ardin, Ifad (School of Business and Management Institut Teknologi Bandung, 2010)
Gudang Garam and Sampoerna are the biggest cigarette companies in Indonesia. Both ofthem haveboth incumbent and new brands. Gudang Garam has Surya 16 as its incumbentbrand and just released Surya Slim as its new brand, while Sampoerna has A Mild as itsincumbent brand and introduced Avolution as its new brand. The companies pursued differentapproaches in introducing the new brands.Print ads are the main source of information abouttheir strategy. It conveys messages about value to be offfered to the market. Analysis of visualand text or copy elements of the ads are analyzed and mapped into the Consumer PerceivedValue (CPV) framework from Sweeney & Soutar. The framework is divided into fourdimensions: emotional, social, quality and value for money. Qualitative analysis shows howthe two companies introduced their new brands and its relation to the incumbent brands.Keywords:brand, innovation, consumer perceived value, advertising, cigarette industry